1994
DOI: 10.1159/000154195
|View full text |Cite
|
Sign up to set email alerts
|

DNA Polymorphisms of the Cholesteryl Ester Transfer Protein (CETP) Gene in Italian and Greek Migrants to Australia

Abstract: The distribution of two common TaqIrestriction fragment length polymorphisms (RFLPs) of the cholesteryl ester transfer protein (CETP) gene were determined in 271 Italian-born and 170 Greek-born migrants to Melbourne, Australia. A much smaller number were examined for the EcoNl RFLP of the same gene. Allele frequencies of the TaqlA RFLP exhibited the least variation in both ethnic groups, and no significant regional heterogeneity in allele or genotype frequencies of either TaqlRFLP was detected for Greece or It… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

5
28
1

Year Published

1998
1998
2015
2015

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(34 citation statements)
references
References 8 publications
5
28
1
Order By: Relevance
“…The less-common allele of this SNP has been shown to be associated with lower CETP and higher HDL levels across numerous studies and populations with highly significant P values (45,49,53,60,. Only in studies with small test populations has neither CETP nor HDL been affected in a statistically significant manner (43,(93)(94)(95)(96)(97)(98)(99)(100)(101)(102)(103)(104)(105)(106)(107). Since it is not immediately apparent how this SNP could modulate CETP expression, it has long been suspected that this SNP is linked with another change that more directly affects expression.…”
Section: Wild-type Proteinmentioning
confidence: 99%
“…The less-common allele of this SNP has been shown to be associated with lower CETP and higher HDL levels across numerous studies and populations with highly significant P values (45,49,53,60,. Only in studies with small test populations has neither CETP nor HDL been affected in a statistically significant manner (43,(93)(94)(95)(96)(97)(98)(99)(100)(101)(102)(103)(104)(105)(106)(107). Since it is not immediately apparent how this SNP could modulate CETP expression, it has long been suspected that this SNP is linked with another change that more directly affects expression.…”
Section: Wild-type Proteinmentioning
confidence: 99%
“…It has been suggested that these associations may be population related (Tenkanen et al, 1991;Mitchell et al, 1994) and highly influenced by environmental factors, such as tobacco smoking (Kauma et al, 1996). Also, Kuivenhoven et al (1998) showed interactions between the TaqI genotype and the progression of coronary heart disease (CHD) after therapy.…”
Section: Introductionmentioning
confidence: 99%
“…10 The B2 allele (absence of the TaqI restriction site) at this polymorphic site has been associated in normolipemic subjects with increased HDL cholesterol (HDL-C) levels and decreased CETP activity and levels, 13-16 thus resembling a mild form of CETP deficiency. It has been suggested that this association may be population specific 17,18 and highly influenced by environmen- …”
mentioning
confidence: 99%
“…10 The B2 allele (absence of the TaqI restriction site) at this polymorphic site has been associated in normolipemic subjects with increased HDL cholesterol (HDL-C) levels and decreased CETP activity and levels, [13][14][15][16] thus resembling a mild form of CETP deficiency. It has been suggested that this association may be population specific 17,18 and highly influenced by environmen-tal factors, such as alcohol consumption and tobacco smoking. 15,19,20 Moreover, Kuivenhoven et al 21 have shown an interaction between the TaqIB genotype and the progression of coronary heart disease (CHD) after therapy.…”
mentioning
confidence: 99%